Implementasi Manajemen Distribusi Dana Zakat, Infak, dan Sedekah: Studi Kasus NU Care-Lazisnu Kabupaten Magelang - Yahya Nur Hidayat; Pudail Pudail; Qurotul Aini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The Nahdlatul Ulama Zakat Infaq and Alms Amil Institute (LAZISNU) is an institution that focuses on collecting, distributing and utilizing zakat, infaq and alms. This research aims to develop strategies for utilizing zakat, infaq and alms funds in NU CARE-LAZISNU, Magelang Regency. The research method used is a qualitative descriptive approach, with data collection techniques through observation, interviews and documentation. The results of the research show that NU CARE-LAZISNU Magelang Regency received income from zakat, infaq and alms as follows: IDR 284,678,815 in 2020, IDR 11,692,068,596 in 2021, and IDR 775,202,741 in 2023. Management of funds carried out by the zakat infaq and alms amil institution (LAZISNU) through programs covering the social, religious, health, education and disaster response fields, using nu coins as the main source of collecting funds. The funds collected are collected and distributed in accordance with the NU CARE-LAZISNU work program. The management of zakat funds is carried out professionally and transparently. These programs include direct assistance to individuals in need, construction of infrastructure, and support for religious and social activities. The programs implemented by NU CARE-LAZISNU Magelang Regency have had a positive impact on the beneficiary communities.